2012
DOI: 10.1103/physreva.85.013602
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-Taylor instability in a two-component Bose-Einstein condensate with rotational symmetry

Abstract: The interfacial instability and subsequent dynamics in a phase-separated two-component Bose-Einstein condensate with rotational symmetry are studied. When the interatomic interaction or the trap frequency is changed, the Rayleigh-Taylor instability breaks the rotational symmetry of the interface, which is subsequently deformed into nonlinear patterns including mushroom shapes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
0
35
0
5
Order By: Relevance
“…Whereas other studies have characterized the IMT of dipolar Bose gases via full mean-field simulations in one dimension [28] and Monte-Carlo simulations in twodimensions [29], we perform full mean-field simulations in addition to an analytic Bogoliubov treatment, allowing us to characterize the IMT very efficiently in a large parameter space. Additionally, we note that other theoretical works on non-dipolar binary BECs have predicted finite wavelength phenomenon regarding, for example, the boundaries of immiscible systems [30][31][32][33] and quenches deep into immiscible parameter space [34]. These phenomena, however, are not roton-like in that the threshold defining the transition parameters is determined by long-wavelength, or phonon-like excitations in each case.…”
Section: Introductionmentioning
confidence: 95%
“…Whereas other studies have characterized the IMT of dipolar Bose gases via full mean-field simulations in one dimension [28] and Monte-Carlo simulations in twodimensions [29], we perform full mean-field simulations in addition to an analytic Bogoliubov treatment, allowing us to characterize the IMT very efficiently in a large parameter space. Additionally, we note that other theoretical works on non-dipolar binary BECs have predicted finite wavelength phenomenon regarding, for example, the boundaries of immiscible systems [30][31][32][33] and quenches deep into immiscible parameter space [34]. These phenomena, however, are not roton-like in that the threshold defining the transition parameters is determined by long-wavelength, or phonon-like excitations in each case.…”
Section: Introductionmentioning
confidence: 95%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32], The interfacial phenom om enology in Bose m ixtures has been explored in Refs. [33][34][35][36][37][38][39][40] and the phase diagram at finite tem perature was investigated in Refs. [41][42][43][44], O ur focus in this paper is on the calculation o f static interfa cial properties o f BEC binary m ixtures w ithin G ross-Pitaevskii (GP) theory [45].…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be a difference in the temperature at which the condensed components are initially held (if condensed separately), and there can easily be situations in which nonequilibrium dynamics are prevalent. A number of studies have reported the development of fundamental instabilities in two-component condensates, such as collective oscillations in colliding condensates [36,37], Rayleigh-Taylortype instabilities [38][39][40], Kelvin-Helmholtz-type instabilities [41,42], counter-superflow instabilities [43,44], and crossovers between Kelvin-Helmholtz-type instabilities and countersuperflow instabilities [45]. A separate line of studies has focused on "exotic" condensates, such as the spin-orbit condensate [46][47][48], the two-or three-component condensate with a Rabi coupling [49,50], spin-orbit together with Rabi coupling [51], and dipole-dipole interactions in two-component condensates [52].…”
Section: Introductionmentioning
confidence: 99%